Peningkatan Efisiensi Produksi Dan Daya Saing Produk Keripik Singkong UMKM - Sri Kusumastuti; Sindung Hadwi Widi Sasono; Raditya Artha Rochmanto; Vinda Setya Kartika (CV. Multi Kreasi Media, 2026)
Micro, Small, and Medium Enterprises (MSMEs) producing cassava chips in Rejosari, Trisobo, Boja, Kendal Regency have significant economic potential due to the availability of local raw materials. However, manual production processes and simple packaging limit production efficiency and product competitiveness. This program aimed to improve production efficiency, product quality, and competitiveness through the application of appropriate technology combined with training and assistance. The implementation methods included problem identification, application of a cassava slicing machine, training on production equipment usage, packaging training using a plastic sealer, product labeling, and monitoring and evaluation. The results show that the cassava slicing machine significantly reduced processing time and produced more uniform slices. Packaging and labeling training improved product hygiene, appearance, and identity. Overall, the program positively impacted production efficiency, packaging quality, and the competitiveness of MSME cassava chip products in the local market.